INTEGRATION OF ISLAMIC DIETARY PATTERNS AND LIFESTYLE IN CONTROLLING THE HEALTH OF STUDENTS IN MODERN ISLAMIC BOARDING SCHOOLS - Muhammad Afwan Romdloni (Hijri, 2025)
Modern Islamic boarding schools are residential-based educational environments that play a strategic role in shaping students’ dietary patterns and lifestyles. The integration of Islamic values into daily life has the potential to serve as an effective approach to controlling students’ health. This study aims to analyze the integration of Islamic dietary patterns and lifestyle as a strategy for health control among students in modern Islamic boarding schools. The study employed a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. Research informants consisted of students and boarding school administrators selected using purposive sampling. Data were analyzed using thematic analysis to identify patterns and meanings emerging from students’ daily practices. The findings indicate that Islamic dietary patterns—encompassing the principles of halal and thayyib, eating etiquette, and moderation—along with Islamic lifestyles reflected in discipline, personal hygiene, and religious routines, contribute positively to students’ health control. The boarding school environment and the role-modeling of administrators play a crucial role in shaping healthy behaviors among students. However, limitations were still identified, particularly in terms of menu variety and nutritional understanding. This study concludes that the integration of Islamic dietary patterns and lifestyle has strong potential as a promotive and preventive strategy for improving students’ health in modern Islamic boarding schools.